(untitled) (Balneo and PRM Research Journal, 2022)
ABSTRACT: The article presents the results of studies of the effect of radon and sulfide mineral waters (MW) on Wistar rats with experimental arthrosis. materials and methods. Rats were randomized into 4 groups. Group 1 consisted of intact rats (control group). In the remaining three groups, a model of knee arthrosis was reproduced using dexamethasone injections. Group 2 consisted of rats with untreated pathology. Group 3 consisted of rats using radon MW procedures, and group 4 consisted of rats using sulfide MW. Results. Morphological studies have determined that using radon and sulfide MW has a curative effect on the structural and functional organization of the joint and cartilage - the manifestations of inflammation in the knee joints are significantly reduced, dystrophic manifestations disappear, and reparative processes in cartilage improve. There are signs of an improvement in the state of metabolic processes in the body of rats: the balance in the lipid peroxidation and antioxidant systems is restored, and the indicators of the processes of energy supply of transmembrane transport (according to the activity of magnesium-dependent Na+/K+-ATP-ase and Ca2+-ATP-ase) and protein exchange.Conclusion. Based on the data obtained, it was concluded that both applied MWs have a unidirectional, but somewhat different in strength, curative effect on the course of experimental arthrosis, which is due to different mechanisms of the biological action of radon and hydrogen sulfide.